PERENCANAAN KEBUTUHAN MATERIAL MENGGUNAKAN METODE LOT-SIZING DENGAN PENERAPAN METODE FORECASTING TIME SERIES DALAM PERENCANAAN PRODUKSI DI KONVEKSI XYZ - Anggela, Pepy; Febriandini, Febriandini; Wahyudi, Tri (Teknik Industri Unikom, 2022)
XYZ convection is an industry that is engaged in the production as well as marketing or selling robes. This business was founded in 2012 in Sambas Regency, West Kalimantan. Based on historical data obtained, the demand for robes at XYZ Convection has fluctuated erratically, causing companies to sometimes produce in excess quantities and produce in insufficient quantities, resulting in non-optimal sales activities. The purpose of this research is to optimize the production plan to meet future demand. The stages in this research are data collection, plotting data, forecasting using the time series method, conducting validation tests on the selected method, making RRP, doing aggregate planning, making master production schedule, making RCCP and planning material requirements using 4 lot methods. sizing methods, namely the LFL, EOQ, POQ and FPR methods. The results showed that the best method was the centered moving average method, because it had the smallest MSE value of 4050.13, the smallest MAD was 47.11 and the smallest MAPE was 11.06%. The total cost required for the production of robes for 12 periods is IDR 319,120,000.00. While the planning of raw material requirements used the LFL method and the POQ method, with the total cost of the raw material for the robes needed for the next 12 periods, which is Rp. 428,884,300. The cost for each raw material is Rp. 456,460,000 for fabric, Rp. 10,448,000 for zippers, 1,036,000 for buttons, Rp 1,840,000 for vislin, sewing thread for Rp. 7,836,000 and thread sale of Rp. 5,224,000. . So the impact of this research is, it can minimize the cost of raw material needs.